Influence of environmental variables on the tree community structure and floristic patterns in a montane Araucaria Forest fragment in lages, Santa Catarina state Influência de variáveis ambientais sobre o padrão estrutural e florístico do componente arbóreo, em um fragmento de floresta ombrófila mista montana em lages, SC - Higuchi, Pedro (2012)
This study aimed to characterize the floristic composition and structure of the tree component of a montane Araucaria Forest fragment and to assess the influence of environmental variables on the patterns observed. The study area was located in the municipality of Lages, Santa Catarina state, close to the margin of the Caveiras River. The vegetation and the environmental variables (physical and chemical soils characteristics, relief and canopy cover) were surveyed within 50, 20 × 10m, permanent plots allocated systematically stratified in the forest fragment. All trees with circumference at breast height (CBH) ≥ 15,7 cm were measured (CBH and height) and identified. The importance values (IV) of the found species were calculated, the plots and species were ordinated by an analysis of NMDS (Nonmetric Multidimensional Scaling), according to the abundance of species, and the significant environmental variables plotted "a posteriori" in the ordination diagram. One thousand, eight hundred and forty-three (1,843) individuals were sampled, which added up to a total basal area of 36.45 m 2, distributed in 37 botanical families, 63 genera and 92 species. The three species with the highest values of VI were Araucaria angustifolia (Bertol.) Kuntze, Lithraea brasiliensis Marchand and Jacaranda puberula Cham. The variables that showed the higher correlation with the tree component structure and floristic composition were the pH, the plot highest declivity and the Mg content.